Improving selection of markers in nutrition research: evaluation of the criteria proposed by the ILSI Europe Marker Validation Initiative. Issue 1 (16th February 2017) - Calder, Philip C.; Boobis, Alan; Braun, Deborah; Champ, Claire L.; Dye, Louise; Einöther, Suzanne; Greyling, Arno; Matthys, Christophe; Putz, Peter; Wopereis, Suzan; Woodside, Jayne V.; Antoine, Jean-Michel
Abstract: The conduct of high-quality nutrition research requires the selection of appropriate markers as outcomes, for example as indicators of food or nutrient intake, nutritional status, health status or disease risk. Such selection requires detailed knowledge of the markers, and consideration of the factors that may influence their measurement, other than the effects of nutritional change. A framework to guide selection of markers within nutrition research studies would be a valuable tool for researchers. A multidisciplinary Expert Group set out to test criteria designed to aid the evaluation of candidate markers for their usefulness in nutrition research and subsequently to develop a scoring system for markers. The proposed criteria were tested using thirteen markers selected from a broad range of nutrition research fields. The result of this testing was a modified list of criteria and a template for evaluating a potential marker against the criteria. Subsequently, a semi-quantitative system for scoring a marker and an associated template were developed. This system will enable the evaluation and comparison of different candidate markers within the same field of nutrition research in order to identify their relative usefulness. The ranking criteria of proven, strong, medium or low are likely to vary according to research setting, research field and the type of tool used to assess the marker and therefore the considerations for scoring need to be determined in a setting-, field- and tool-specific manner. A database of such markers, their interpretation and range of possible values would be valuable to nutrition researchers.